2021
DOI: 10.1587/elex.18.20210302
|View full text |Cite
|
Sign up to set email alerts
|

A 56-Gbps PAM4 amplitude-rectification-based receiver with threshold adaptation and 1-tap DFE

Abstract: This paper presents a 56-Gbps four-level pulse amplitude modulation (PAM4) quarter-rate receiver based on amplitude rectification. Compared with the conventional three-comparator structure, the PAM4 signal is converted into a 2-digit gray-code rather than a 3-digit thermometer-code. The amplitude is detected to decode the least significant bit (LSB), which allows the proposed receiver to use significantly less power by reducing the number of comparators. An inverter-based common-mode voltage stabilization circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To satisfy the stringent bandwidth requirement while improving the spectral efficiency, IEEE 802.3bs recommends PAM4 signaling to fulfill 200/400 Gb/s Ethernet by employing 4×50 Gb/s and 8×50 Gb/s multi-channel links [3,4]. The PAM4 signaling encodes the most significant bit (MSB) and the least significant bit (LSB), into one single symbol, thus enhancing the spectral efficiency and mitigating the bandwidth limitation for both channel and front-end circuit [5,6]. Nevertheless, the PAM4 signaling exhibits a more severe inter-symbol interference (ISI) due to the in-trinsic 9.5 dB signal-to-noise ratio (SNR) penalty [7,8] and 12 different transitions compared to NRZ format.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy the stringent bandwidth requirement while improving the spectral efficiency, IEEE 802.3bs recommends PAM4 signaling to fulfill 200/400 Gb/s Ethernet by employing 4×50 Gb/s and 8×50 Gb/s multi-channel links [3,4]. The PAM4 signaling encodes the most significant bit (MSB) and the least significant bit (LSB), into one single symbol, thus enhancing the spectral efficiency and mitigating the bandwidth limitation for both channel and front-end circuit [5,6]. Nevertheless, the PAM4 signaling exhibits a more severe inter-symbol interference (ISI) due to the in-trinsic 9.5 dB signal-to-noise ratio (SNR) penalty [7,8] and 12 different transitions compared to NRZ format.…”
Section: Introductionmentioning
confidence: 99%
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15]. However, the reduced symbol levels render the PAM-4 scheme less tolerant to the residual inter-symbol interference and amplitude noise [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LE amplifies the noise and signal together, which does not improve the BER performance of the communication system [14,15,16]. Based on the above reasons, DFE is mainly used to eliminate residual ISI together with LE [17,18]. DFE only amplifies the signal but not the noise, which can effectively improve SNR characteristic.…”
Section: Introductionmentioning
confidence: 99%